Régiók, regionalizmus, gazdasági kapcsolatok és azok előzményei a mai Európában = Region, regionalism, economic relations in today's Europe - Dömők Csilla (2017)
Regions and regionalism are rather flourishing in Europe. But what do regionalism and the expression “Europe of regions” exactly mean? There are three approaches to the question: first, the concept of cross-border interregionality between the Member States of the European Union; second, the effort to make regions the basic building blocks of European integration instead of states; and finally, the objective to introduce a three-tier structure to the European Union which would extend the already existing tiers of the European Union and the Member States with a third one, the territorial units within nation-states. The first approach (interregional cooperation) has long been adopted; the second approach (the vision of Europe made up of regions instead of states) is rather utopian. The third one is subject to fierce debates: a three-tier European Union with European, nation-state and regional levels. Although the form, motives and causes of movements promoting regionalism may vary greatly, 1 their purpose is the same for autonomous, federalist and separatist movements alike: to relativise the existing central nation-state. Thus, advancing European integration has become a natural ally for them as – from their perspective – it meant the disfunctionality of traditional nation-states. A supranational and therefore multinational and multicultural community promises much more room for development than a classic nation-state.